Универсальное хеширование по кривым Гурвица - Халимов, Г. З. (ХНУРЭ, 2008)
Presents result research to curves for target universal hashing up to CarterVegman, parameters valuation algebraic curve Hurvitz.
Keywords: универсальное хеширование; кривые Гурвица